Obstetric hysterectomy: analysis of 50 cases at a tertiary care hospital - Mayadeo, Niranjan M.; Swaminathan, Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Despite advances in modern medical sciences, there is a plethora of morbidity which continues to affect women during childbirth, necessitating removal of the uterus in the peripartum or postpartum period. This study analyses 50 cases of obstetric hysterectomy done in a single institute. Methods: After Institutional Ethics Committee approval, a retro prospective analysis of hospital records of 50 cases of obstetric hysterectomy was done over a five year period in the department of obstetrics and gynaecology at a tertiary care referral centre-KEM hospital. Results: During the study period, there were 50 cases of obstetric hysterectomy out of 43839 deliveries giving an incidence of 0.12%. Mean age of women undergoing obstetric hysterectomy was 29.9 years. 86% of these were multiparous. The most common indication was morbidly adherent placenta (38%) followed closely by followed by rupture uterus (34%) and uterine atony (20%). Total hysterectomy was the most preferred type of hysterectomy (74%). Urinary tract injury and hypovolemic shock were the most frequently encountered complications. The maternal mortality rate in our study was 4%. 86% of the babies born had Apgar score of 9/10. 44% of babies required admission to neonatal intensive care unit.19.6% of the patients had still born babies and there were 4 neonatal deaths. Conclusions: Obstetric hysterectomy is associated with increased risk of maternal and perinatal morbidity and mortality.